Relationship of Gaming Disorder with parenting based on low affection-communication and personality trait of neuroticism in adolescents - Rodríguez-Ruiz, Francesc; Marí-Sanmillán, María Isabel; Benito, Ana; Castellano-García, Francisca; Sánchez-Llorens, Marta; Almodóvar-Fernández, Isabel; Haro, Gonzalo (Frontiers in Psychology, 2023)
Background: Gaming Disorder is increasingly common in adolescents. We aimed to evaluate the relationship between parenting, personality traits and Gaming Disorder. Methods: an observational and cross-sectional study in 6 secondary schools of Castelló, obtaining a final sample of 397 students. Results: Adolescents with Gaming Disorder had lower scores in Adolescent Affection-Communication (F = 8.201; p < 0.001), Father’s Warmth (F = 3.459; p = 0.028), and Father’s Acceptance/Involvement (F = 5.467; p = 0.003) and higher scores in Mother’s Revoking Privileges (F = 4.277; p = 0.034) and Father’s Indifference (F = 7.868; p = 0.002) than healthy participants. Male sex was a risk factor for Gaming Disorder (OR = 12.221; p = 0.004), while Adolescent Affection-Communication (OR = 0.908; p = 0.001) and Agreeableness (OR = 0.903; p = 0.022) were protective factors. Data modelling described the protective effect that Adolescent Affection-Communication had on Gaming Disorder, which was both directly (B = −0.20; p < 0.001) and indirectly mediated by Neuroticism (B = −0.20; p < 0.001), while Neuroticism itself was a risk factor for Gaming Disorder (B = 0.50; p < 0.001). Conclusion: These results reflect that Parental style with low affection and communication was directly and indirectly related to the Gaming Disorder, as well as male sex and personality trait of Neuroticism.